Analysis of source regions and transport pathways of sub-micron aerosol components in Europe - Michelle Y. Schneider; Jianhui Jiang; Ying Chen; Wenche Aas; Samira Atabakhsh; Minna Aurela; Claudio Belis; Aikaterini Bougiatioti; Michael Bressi; Francesco Canonaco; Benjamin Chazeau; Hasna Chebaicheb; et al. (Environmental Pollution, 2025)

Revisiting the impact of temperature on ground-level ozone: A causal inference approach - Baihua Chen; Ling Zhen; Lin Wang; Haobin Zhong; Chunshui Lin; Lin Yang; Wei Xu; Ru-Jin Huang (Science of The Total Environment, 2024)

Understanding the variability of ground-level ozone and fine particulate matter over the Tibetan plateau with data-driven approach - Haobin Zhong; Ling Zhen; Lin Yang; Chunshui Lin; Qiufang Yao; Yanping Xiao; Qi Xu; Jinsong Liu; Baihua Chen; Haiyan Ni; Wei Xu (Journal of Hazardous Materials, 2024)

Convergent Neuroimaging and Molecular Signatures in Mild Cognitive Impairment and Alzheimer’s Disease: A Data-Driven Meta-Analysis with N = 3,118 - Xiaopeng Kang; Dawei Wang; Jiaji Lin; Hongxiang Yao; Kun Zhao; Chengyuan Song; Pindong Chen; Yida Qu; Hongwei Yang; Zengqiang Zhang; Bo Zhou; Tong Han; et al. (Neuroscience Bulletin, 2024)
The current study aimed to evaluate the susceptibility to regional brain atrophy and its biological mechanism in Alzheimer’s disease (AD). We conducted data-driven meta-analyses to combine 3,118 structural magnetic resonance images from three datasets to obtain robust atrophy patterns. Then we introduced a set of radiogenomic analyses to investigate the biological basis of the atrophy patterns in AD. Our results showed that the hippocampus and amygdala exhibit the most severe atrophy, followed by the temporal, frontal, and occipital lobes in mild cognitive impairment (MCI) and AD. The extent of atrophy in MCI was less severe than that in AD. A series of biological processes related to the glutamate signaling pathway, cellular stress response, and synapse structure and function were investigated through gene set enrichment analysis. Our study contributes to understanding the manifestations of atrophy and a deeper understanding of the pathophysiological processes that contribute to atrophy, providing new insight for further clinical research on AD.

Direct emissions of particulate glyoxal and methylglyoxal from biomass burning and coal combustion - Ting Wang; Ru-Jin Huang; Lu Yang; Wenting Dai; Haiyan Ni; Yuquan Gong; Jie Guo; Haobin Zhong; Chunshui Lin; Wei Xu (Science of The Total Environment, 2023)

Relationship Between Perisylvian Essential Language Sites and Arcuate Fasciculus in the Left Hemisphere of Healthy Adults - Yu Lin; Kai Zhang; Shuai Li; Song Li; Jingna Jin; Fang Jin; Wen Qin; Long Hai; Meng Zhu; Chunshui Yu; Zhipeng Liu; Tao Yin; et al. (Neuroscience Bulletin, 2017)